IL‐2 and IL‐15 regulate CD8+ memory T‐cell differentiation but are dispensable for protective recall responses. Issue 12 (2nd November 2015) - Mathieu, Cédric; Beltra, Jean‐Christophe; Charpentier, Tania; Bourbonnais, Sara; Di Santo, James P.; Lamarre, Alain; Decaluwe, Hélène
Abstract : The ability to mount effective secondary responses is a cardinal feature of memory CD8 + T cells. An understanding of the factors that regulate the generation and recall capacities of memory T cells remains to be ascertained. Several cues indicate that two highly related cytokines, IL‐2 and IL‐15, share redundant functions in this process. To establish their combined roles in memory CD8 + T‐cell development, maintenance, and secondary responses, we compared the outcome of adoptively transferred IL2Rβ +/− or IL2Rβ −/− CD8 + T cells after an acute viral infection in mice. Our results demonstrate that both IL‐2 and IL‐15 signals condition the differentiation of primary and secondary short‐lived effector cells by altering the transcriptional network governing lineage choices. These two cytokines also regulate the homeostasis of the memory T‐cell pool, with effector memory CD8 + T cells being the most sensitive to these two interleukins. Noticeably, the inability to respond to both cytokines limits the proliferation and survival of primary and secondary effectors cells, whereas it does not preclude potent cytotoxic functions and viral control either initially or upon rechallenge. Globally, these results indicate that lack of IL‐2 and IL‐15 signaling modulates the CD8 + T‐cell differentiation program but does not impede adequate effector functions.